Evaluation of Students Performance in The Japanese Apprenticeship Program - Kokom Komariah; Badraningsih Lastariwati; Siti Hamidah; Sri Palupi; Tuatul Mahfud; Eltom Ishaq Osman Musa (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Apprenticeship programs are considered as an effective learning method to improve the job skills of prospective workers. The Japanese apprenticeship program highlights 5 work principles consisting of Seiri, Seito, Seiso, Seiketsu, Shitsuke (5S). However, until now, the apprenticeship program's effectiveness in Japan to foster 5S work principles for students has not been much evaluated. The objectives of this study were (1) to describe the student's 5S performance profile; (2) factors affecting the implementation of student 5S performance in the apprenticeship program in Japan; (3) the benefits of the Japanese apprenticeship program. This study involved 69 students who were apprenticed in Japan. The data collection used a questionnaire, and the data were analyzed using descriptive analysis. The study results revealed that the student's 5S performance was considered good during the apprenticeship program in Japan. Besides, the study results also show that ten factors affect student performance when participating in an apprenticeship program, namely self-discipline, technology, equipment arrangement, workplace, job planning, worker characteristics, management support, work type, job characteristics, and the existence of training. . Finally, the apprenticeship program in Japan provides benefits to the development of student work competencies which include aspects of knowledge, attitudes, and skills. This study recommends the need to develop and strengthen apprenticeship programs with a positive work culture that can encourage student performance improvement.